Alan Turing's 'Computing Machinery and Intelligence'. - Castelfranchi, Cristiano (Topoi: An International Review of Philosophy, 2013)
The author discusses the principled foundation of cognition and machinery and function by mathematician Alan Turing that led to the foundation of computer science and Artificial Intelligence (AI). He states that Turing attempts to bring the AI field back to its role and origin and to focus on its theoretical and methodological foundations. He says that Turing urge to face technological innovation with open eyes.